A Rare Presentation of In Situ Mantle Cell Lymphoma and Follicular Lymphoma: A Case Report and Review of the Literature - Taverna, Josephine; Nair, Anju; Yun, Seongseok; Paulson, Spencer; Schatz, Jonathan H.; Persky, Daniel; Fuchs, Deborah; Puvvada, Soham (Case Reports in Hematology, 2014)
A 65-year-old gentleman presented with left groin swelling over the course of two months. Physical exam revealed nontender left inguinal adenopathy, and computed tomography scans detected multiple lymph nodes in the mesenteric, aortocaval, and right common iliac regions. An excisional lymph node biopsy was performed. Pathologic evaluation demonstrated follicular center site which stained positive for PAX5, CD20, CD10, Bcl-2, Bcl-6, and mantle zone cells. These findings demonstrated CCND1 and CD5 positivity, suggesting composite lymphoma comprising follicular lymphoma (FL) with in situ mantle cell lymphoma (MCLIS). FL is known as indolent non-Hodgkin lymphoma; however, the clinical significance of a coexisting MCLIS continues to be elusive, and optimal management of these patients remains largely unknown. This case illustrates the diagnostic and therapeutic challenges of composite lymphomas. This paper also discusses advances in molecular pathogenesis and lymphoma genomics which offer novel insights into these rare diseases.